1994
DOI: 10.1073/pnas.91.18.8562
|View full text |Cite
|
Sign up to set email alerts
|

Divergent T-cell cytokine patterns in inflammatory arthritis.

Abstract: A major immunoregulatory mechanism in inflammatory infections and allergic dies Is the control of the balance of cytokines secreted by Thl/Th2 subsets of T helper (Th) cells. This might also be true in autoimmune diseas; a Th2 pattern that prevents an effective immune response in infections with intracellular bacteria may favor immunosuppression in autoimmune disease. The pattern of cytokine expression was compared in the synovial tissue from patients with a typical autoimmune disease, rheumatoid arthritis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
163
5
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(185 citation statements)
references
References 48 publications
15
163
5
2
Order By: Relevance
“…Considerable evidence, however, supports the notion that CD4 T cells from patients with RA express some striking abnormalities in their differentiation into effector cells, in their functional capabilities, and in their responsiveness to regulatory forces. A shift in the Th1/ Th2 balance toward Th1 has been described in patients with RA, and this also has prognostic value for the course of the disease (26,27). In our previous study, we identified an impaired capacity of RA CD4 T cells to differentiate into Th2 cells at the onset of the disease (28), which could potentially contribute to the evolution of sustained autoimmune inflammation.…”
Section: Discussionmentioning
confidence: 84%
“…Considerable evidence, however, supports the notion that CD4 T cells from patients with RA express some striking abnormalities in their differentiation into effector cells, in their functional capabilities, and in their responsiveness to regulatory forces. A shift in the Th1/ Th2 balance toward Th1 has been described in patients with RA, and this also has prognostic value for the course of the disease (26,27). In our previous study, we identified an impaired capacity of RA CD4 T cells to differentiate into Th2 cells at the onset of the disease (28), which could potentially contribute to the evolution of sustained autoimmune inflammation.…”
Section: Discussionmentioning
confidence: 84%
“…Further, treatment of monocytes with interferon-␥ (IFN␥) resulted in increased cell surface expression of both TLR-2 and TLR-4 (18,42), and IFN␥ sensitized the monocytes to respond to LPS (43). Although the levels of IFN␥ detected in SF of patients with established RA were low (44), IFN␥ mRNA was present in synovial tissue lymphocytes (45), and it is possible that IFN␥ contributes to sensitizing macrophages to express increased levels of TLR-2 and TLR-4 in vivo. Other cytokines expressed locally, including IL-10 and macrophage colonystimulating factor, may also contribute to the increased TLR-2 expression in the RA joint (17).…”
Section: Discussionmentioning
confidence: 99%
“…The decreased CD40 expression is likely to result from ligand-induced receptor endocytosis inasmuch as CD40 mRNA levels are comparable (as demonstrated by Northern blot analysis) in cells that are cultured without or with L-CD40 L (data not shown). The presence of IFN--producing cells [34,35] within the synovium and the CD40-inducing capacity of IFN-may explain why CD40 expression on rheumatoid synovial pannus was so easily detected.…”
Section: Discussionmentioning
confidence: 99%